Financing disaster risk reduction in Asia and the Pacific a guide for policy makers. (Metro Manila, Philippines Asian Development Bank, 2020)
Disaster events impact Asia and the Pacific more than any other region in the world. In light of current and future climate and disaster risks, there is an urgent need to address the region underinvestment in disaster risk and reduction. The publication provides an overview of financing opportunities for developing Asia including instruments and mechanisms as well as country case studies and practical tips for governments to implement enhanced disaster risk reduction.
Keywords: Climatic change; Disaster risk management; Electronic books